War and the health of nations - Iqbal, Zaryab, 1974- (Stanford University Press, 2010)
Assessments of the costs of war generally focus on the financial, political, military, and territorial risks associated with involvement in violent conflict. Often overlooked are the human costs of war, particularly their effects on population well-being. This book explores these human costs by offering a large-scale empirical study of the relationship between armed conflict and population health.